ROS-talk – how the apoplast, the chloroplast, and the nucleus get the message through - Shapiguzov, Alexey; Vainonen, Julia; Wrzaczek, Michael; Kangasjärvi, Jaakko (Frontiers in Plant Science, 2012)
The production of reactive oxygen species (ROS) in different plant subcellular compartments is the hallmark of the response to many stress stimuli and developmental cues. The past two decades have seen a transition from regarding ROS as exclusively cytotoxic agents to them being considered as reactive compounds which participate in elaborate signalling networks connecting various aspects of plant life. We have now arrived at a stage where it has become increasingly difficult to disregard the communication between different types and pools of ROS. Production of ROS in the extracellular space, the apoplast, can influence ROS generation in the chloroplast and both can regulate nuclear gene expression. In spite of existing information on these signalling events, we still barely grasp the mechanisms of ROS signalling and communication between the organelles. In this review we summarize evidence that supports the mutual influence of extracellular and chloroplastic ROS production on nuclear gene regulation and how this interaction might occur. We also reflect on how and via which routes signals might reach the nucleus where they are ultimately integrated for transcriptional reprogramming. New ideas and approaches will be needed in the future to address the pressing questions of how ROS as signalling molecules can participate in the coordination of stress adaptation and development and how they are involved in the chatter of the organelles.